Confusion or fusion? Cultural diversity in the cosmopolitan translation of Chinese street food names in Malaysia - Zhu, Hongxiang; Ang, Lay Hoon (Routledge, 2025)
The translation quality of food-related names brings with it much discussion. However, from a cultural perspective, a confusing translation may not solely stem from an actual issue of quality. This study aims to explore the practice of language use in the translations of street food names and examine the possible reasons and implications. Cosmopolitan translation embraces cultural difference and reveals an openness to other cultural elements. This study conducts a qualitative ethnographic study that utilises content analysis and semi-structured interviews concerning the translation of street food names in Malaysia from Chinese to English. This study found that diverse languages were adopted for the translation of street food names–including English, Chinese, Malay, Thai, Japanese, and Korean. The translation creates a cosmopolitan openness to and representation of many diverse cultures. A 3M model for the implications of the cosmopolitan translations is proposed from Macro (the multilingual and multicultural setting of Malaysia), Meso (the language used in translation), and Micro perspectives (the cosmopolitan competence of Chinese Malaysians). In conclusion, this study shows that cultural diversity is not simply a source of translation problems and can be concurrently employed as the solution for facing the challenge of the multicultural question.